Reconstruction of 3D structural models for carotid lumen based on B-mode images - Jorge M. S. Pereira (2012)
The most common imaging systems used to study and diagnosis atherosclerosis are the pulse-echo ultrasound imaging systems, in particular the two-dimensional ultrasound B-Mode image systems. However, the images acquired by such systems have reduced quality, mainly low contrast and significant noise that impose several challenges in their processing and analysis. Atherosclerosis is one of the main causes of cerebrovascular accidents, as it affects the blood supply trough the arteries. Previous studies about the hemodynamic profile of the carotid artery have shown to be useful to understand the process of the disease. However, to support realistic biomechanical studies concerning the blood flow, accurate 3D structural models for the carotid artery understudy must be built. In this work, an automated computational solution to segment the carotid lumen in B-Mode images and build the correspondent 3D structural model has been developed. The solution is based on morphological and spatial image features and has two main steps: Firstly, the carotid lumen represented in the input B-mode image is automated detected and segmented. Secondly, the building of the 3D structural model for the carotid lumen segmented is carried out. Experimental results confirm the efficient of the solution developed, and the good results obtained when used in B-mode images.